Analisis Teori Klasik Sosiologi Pendidikan: Perspektif Fungsionalisme, Konflik, dan Interaksionisme - Munziah Munziah; Niken Frofidasari Niken; Muhammad Yasin (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2025)
Education is not merely a space for transferring knowledge, but a social arena that shapes values, norms, and collective identity. This study uses a sociological perspective on education to examine the dynamics of Indonesian education through three main theories: functionalism, conflict, and symbolic interactionism. The research was conducted using a qualitative approach through a literature review of academic works from 2005–2025. The results of the study indicate that functionalism views education as a tool for social integration that maintains order through the transmission of shared values. Conflict theory highlights the role of education in reproducing inequality through differences in access and opportunity, while still opening up critical space to challenge domination. Meanwhile, symbolic interactionism explains how the meaning of education is formed from everyday interactions, symbols, language, and labeling processes that influence student identity. Overall, education needs to be read multidimensionally: as a system supporting order, an arena for competing interests, and a symbolic space that shapes the character of generations.